Application of WeChat-based cognitive behavioural stress management for early-stage cervical cancer patients: a randomised controlled study - Qing Hao; Lan Feng; Dandan Chen; Xia Fan; Lei Wei; Zhaojun Cui; Jing Zhang; Lin Wang; Dan Zhang; Xinxin Zhan; Wenping Yang (Taylor & Francis Group, 2024)
Background This randomised controlled study was aimed at investigating the effects of WeChat-based cognitive behavioural stress management (WB-CBSM) on the mental health of patients with early-stage cervical cancer treated with surgical resection.Methods A total of 184 patients with early-stage cervical cancer were randomised to receive either WB-CBSM (n = 92) or normal care (NC) (n = 92) for 8 weeks.Results Compared with the NC group, the WB-CBSM group exhibited reduced Hospital Anxiety and Depression Scale (HADS)-anxiety scores at months (M)1 (t = 2.022, P = 0.045), M3 (t = 2.575, P = 0.011), and M6 (t = 2.709, P = 0.007); anxiety rates at M3 (χ2 = 4.834, P = 0.028) and M6 (χ2 = 5.182, P = 0.023); HADS-depression scores at M3 (t = 2.069, P = 0.040) and M6 (t = 2.449, P = 0.015); and depression rates at M6 (χ2 = 4.268, P = 0.039). Moreover, the WB-CBSM group showed increased Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being scale scores at M1 (t = −2.001, P = 0.047), M3 (t = −2.281, P = 0.024), and M6 (t = −3.501, P = 0.001); the Quality of Life Questionnaire-Core 30 (QLQ-C30) global health score at M3 (t = −2.034, P = 0.043) and M6 (t = −2.426, P = 0.016); and QLQ-C30 function score at M3 (t = −2.009, P = 0.046). However, the groups exhibited decreased EuroQol-5 dimension scores at M3 (t = 2.056, P = 0.041) and M6 ((t = 2.242, P = 0.026) and QLQ-C30 symptom scores at M1 (t = 2.026, P = 0.044) and M3 (t = 2.210, P = 0.028).Conclusion WB-CBSM reduced anxiety and depression and improved the spiritual well-being and quality of life of patients with early-stage cervical cancer treated with surgical resection.